Penilaian tingkat keberhasilan perawatan ortodontik dengan piranti lepasan berdasarkan indeks PAR Assessment of success rate of orthodontic treatment using removable appliance based on PAR index - Muh. Irwansyah; Eka Erwansyah (DiscoverSys Inc., 2011)
The success of orthodontic treatment, particularly with removable orthodontic appliances not only relies on theexpertise of the clinician, but also highly depends on the patient's own. It is necessary to know the extent of thesuccess rate of an orthodontic treatment. Assessment of malocclusion severity and treatment outcome has become avery popular object of research conducted by the PAR index. This study aims to determine the success rate oforthodontic treatment with removable appliances based on PAR Index. The research was carried out on March-May2011 with samples of patients dental models who had completed orthodontic treatment in the year 2008-2011 at theDepartment of Ortodonsia RSGMP UNHAS. Sixty six pairs of dental models fulfilled the inclusion criteria and therules of PAR Index. Percentage change in PAR score obtained by 35% in the assessment with no weighted and 36%was assessment by weighted. This results showed the level of orthodontic treatment success include into thecategory of